The Choiyoi Group from central Argentina: A subalkaline transitionalto alkaline association in the craton adjacent to the active marginof the Gondwana continent - Llambias, Eduardo Jorge (2003)
Permian and Lower Triassic igneous rocks from La Pampa province, central Argentina, are part of the Choiyoi Group, whose extension in Argentina exceeds 500,000 km2. In La Pampa, the distribution of these outcrops occurs along a NW-SE belt that cuts obliquely across the N-S structures of the Lower Paleozoic rocks. The basement of the Choiyoi Group in western La Pampa consists of Mesoproterozoic to Lower Paleozoic rocks that form part of the exotic Cuyania terrane. In central La Pampa, the basement consists of Lower Paleozoic igneous and metamorphic rocks affected by the Lower Paleozoic Famatinian orogeny.The Choiyoi Group from La Pampa shares features with the Choiyoi Group elsewhere, such as an abundance of mesosilicic to silicic ignimbrites, subvolcanic domes, and granite plutons emplaced at sallow levels. In La Pampa, we recognize two suites: shoshonitic and trachydacitic to rhyolitic. The shoshonite suite is overlain by trachydacites and rhyolites. The plutonic rocks that belong to the cupola of the intrusive bodies are monzogranitic.The most significant difference between the Choiyoi Group from La Pampa and that from the Cordillera Frontal and the San Rafael block is that the San Rafael orogenic phase (Lower Permian) is not obvious in La Pampa. Therefore, we cannot attribute to the Choiyoi Group a postorogenic character, as in the Cordillera Frontal or the San Rafael Block. This difference in the tectonic setting is reflected in the composition of the igneous rocks of La Pampa, in that they generally have a higher alkali content with respect to silica, a weak enrichment in TiO2, and a depletion in CaO. Both suites are transitional from subalkaline to alkaline series.The shoshonitic suite is rich in clinopyroxene and apatite. Whole-rock compositions have high content of P2O5 (0.5-3.9%) and Sr (1320-1890 ppm). Zr is weakly enriched (273-502 ppm), and Nb (29-37 ppm) is depleted. The Th (16-45 ppm) and U (3-14 ppm) content is high.We postulate a crustal origin for the magma with a source with a calc-alkaline signature. The extensional regime that prevailed during the evolution of the Choiyoi Group favors melting processes.